SPECTROSCOPY OF BROAD-LINE BLAZARS FROM 1LAC - Shaw, MS; Romani, R; Cotter, G; Healey, SE; Michelson, P; Readhead, A; Richards, J; Max-Moerbeck, W; King, O; Potter, W (Institute of Physics Publishing, 2012)
We report on optical spectroscopy of 165 flat spectrum radio quasars (FSRQs) in the Fermi 1LAC sample, which have helped allow a nearly complete study of this population. Fermi FSRQs show significant evidence for non-thermal emission even in the optical; the degree depends on the γ-ray hardness. They also have smaller virial estimates of hole mass than the optical quasar sample. This appears to be largely due to a preferred (axial) view of the γ-ray FSRQ and non-isotropic (H/R ∼ 0.4) distribution of broad-line velocities. Even after correction for this bias, the Fermi FSRQs show higher mean Eddington ratios than the optical population. A comparison of optical spectral properties with Owens Valley Radio Observatory radio flare activity shows no strong correlation. © 2012 The American Astronomical Society. All rights reserved.